What motivates public collaborators to become and stay involved in health research? - Toril Beate Røssvoll; Kristin Liabo; Tove Aminda Hanssen; Jan H. Rosenvinge; Elisabeth Sundkvist; Gunn Pettersen (Research Involvement and Engagement, 2024)
Abstract Background People with lived experience of health and illness are increasingly being involved in research. Knowing what creates interest in becoming involved in health research may help identify appropriate ways of facilitating meaningful involvement. The study aimed to investigate why people became public collaborators in health research and what helped sustain their commitment to staying involved. Methods Semistructured individual qualitative interviews were conducted with 11 Norwegian public collaborators recruited from patient organisations. To enhance the quality and relevance of this study, three public collaborators were involved in framing the study and in the data analysis. One of them is a coauthor of this paper. The interviews were analysed through reflexive thematic analysis, and two themes were generated. Results The first theme, ‘research as a vehicle to impact’ showed how interest in becoming involved in research was founded on the possibility of impacting healthcare through research. Other inspiring factors were how they appraised the relevance of the research, in addition to the public collaborators’ own sense of moral duty to advocate for research related to their own as well as others, illnesses or diseases. The second theme, ‘‘Acknowledgement and accessibility’, framed how the participants perceived appreciation of experiential knowledge as crucial for maintaining motivation in their role as public collaborators. Other promoters of sustained involvement presented were training for both public collaborators and researchers, adequate allowance as a means for visualising and valuing PPI, and accessible language. Conclusions This study contributes to the understanding of how to facilitate meaningful and sustainable PPI, which requires a safe space for collaboration and attention to accessibility. Facilitating meaningful involvement may, in turn, increase the potential impact and sustainability of PPI.